2017
DOI: 10.3390/ijerph14060594
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Chemoprophylaxis after Floods to Reduce the Occurrence and Impact of Leptospirosis Outbreaks

Abstract: Record-breaking and devastating rainfall events have occurred in the past decade. Rain and floods are considered the main risk factors for leptospirosis and several outbreaks have been reported following extreme weather events. In such situations, one possible intervention to prevent leptospirosis cases in high-risk groups is the use of chemoprophylaxis. However, not enough evidence of its effect is available. The objectives of this study were to review the literature on the current practices of chemoprophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
0
30
1
1
Order By: Relevance
“…We also conducted the study was also between April and May 2019 when the rainfall in Ibadan was not at its peak. Studies have shown that the prevalence of leptospirosis increases with an increase in rainfall and subsequent flooding [22,28,1,29]. However, we have shown from this study that not all febrile…”
Section: Discussioncontrasting
confidence: 69%
“…We also conducted the study was also between April and May 2019 when the rainfall in Ibadan was not at its peak. Studies have shown that the prevalence of leptospirosis increases with an increase in rainfall and subsequent flooding [22,28,1,29]. However, we have shown from this study that not all febrile…”
Section: Discussioncontrasting
confidence: 69%
“…The current data sources may be fit for purpose as long as these limitations in sensitivity are understood. However, for leptospirosis it is known that early antibiotic treatment of cases is important for reducing morbidity (Schneider et al, ). Consequently, under‐recognition and under‐diagnosis may be contributing to poorer outcomes for infected people and may therefore be a problem that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Over 11 days in late July, we provided 114 raspberry workers, of 230 employed at the time, with four weeks of doxycycline prophylaxis (200 mg weekly). Chemoprophylaxis against leptospirosis has been used in settings such as short‐term exposures in endemic areas or following high‐risk events such as flooding (Schneider et al, ; Sehgal, Sugunan, Murhekar, Sharma, & Vijayachari, ; Takafuji et al, ). However, its use in outbreak control in an occupational context appears novel.…”
Section: Discussionmentioning
confidence: 99%